Non pathological sweat test, pancreatic insufficiency and Cystic Fibrosis: an unusual case in a child with F508del-duplication of exons 1-3 CFTR genotype - Vito Terlizzi; Cristina Fevola; Alice Castaldo; Selene Del Vespa; Daniela Dolce; Luca Scarallo; Karina Kleinfelder; Paola Melotti; Claudio Sorio; Giovanni Taccetti; Paolo Lionetti (BMC, 2024)
Abstract While Cystic Fibrosis is characterized by a high phenotypic variability, a correlation is reported between the pancreatic status and the CFTR genotype. Here we report an unusual case of a child with Cystic Fibrosis (F508del-duplication of exons 1-3 genotype) diagnosed at 8 years old for pancreatic insufficiency and non-pathological sweat test, in absence of respiratory symptoms and acute episodes of pancreatitis. Nasal potential differences and intestinal current measurements were normal, while the short-circuit current measured on patient-derived colonoids grown on Transwell® indicated the presence of a reduced CFTR-dependent current relative to non-CF colonoids with, a modest improvement of CFTR activity record following treatment with elexacaftor/tezacaftor/ivacaftor. This case opens the discussion on the importance of performing CFTR sequencing and the search for large gene rearrangements in cases of pancreatic insufficiency of unclear etiology, also in the presence of non-pathological sweat test. Children with CF and non-pathological sweat chloride are likely to develop higher concentrations if they truly have CF.